RYGB increases postprandial gastric nesfatin-1 and rapid relieves NAFLD via gastric nerve detachment. - Geng Wang; Qingbo Wang; Jie Bai; Gang Li; Kaixiong Tao; Guobin Wang; Zefeng Xia (PLoS ONE, 2020)
Background Roux-en-Y gastric bypass (RYGB) could reduce nonalcoholic fatty liver disease (NAFLD) ahead of the weight-loss effects. But the detailed mechanisms remain unclear. Material and methods A high-fat diet (HFD) was fed to induce obesity. RYGB was then performed. Gastric nesfatin-1 was measured by enzyme-linked immunosorbent assay (ELISA) in portal vein and polymerase chain reaction (PCR) in gastric tissues. Modified surgeries including vagus-preserved bypass and vagectomy were performed and postprandial gastric nesfatin-1 were analyzed. The effects of nesfatin-1 on hepatocytes were studied by PCR and immunohistochemistry. Both intraperitoneal and intracerebroventricular injection (ICV) were performed to analyze the in vivo effects on liver lipid metabolism. Results Increased postprandial portal vein nesfatin-1 was observed in RYGB but not in control groups. This increase is mainly due to induction of gastric nesfatin-1. A modified RYGB in which the gastric vagus is preserved is conducted and, in this case, this nesfatin-1 induction effect is diminished. Mere vagectomy could also induce a similar nesfatin-1 increase pattern. The infusion of nesfatin-1 in the brain could inhibit the expression of gastric nesfatin-1, and the effects are diminished after gastric vagectomy. In vivo and in vitro nesfatin-1 stimulation in the liver resulted in improvements in lipid metabolism. Conclusions Severing the gastric vagus during RYGB could cut off the negative control from the central nervous system (CNS) and result in increased postprandial gastric nesfatin-1 post surgery, which in turn, improves NAFLD.